KEPEMIMPINAN DI ERA KERJA HYBRID: TANTANGAN, PELUANG, DAN STRATEGI EFEKTIF - Budi Sugiarto; Roli Dewanto, Tarsisius Susilo, Setiawan Arismunandar, Edi Wahyudi (ADMIN: Jurnal Administrasi Negara, 2026)
The digital transformation and the evolving work patterns in the post–COVID-19 era have accelerated the emergence of hybrid work models that combine in-office and remote work. This shift requires significant adaptation in organizational leadership styles. This article explores in depth the key challenges faced by leaders in hybrid environments, including communication barriers, the preservation of organizational culture, equitable access, and the management of distributed team performance. Conversely, it also highlights the opportunities brought forth, such as the acceleration of digital transformation, greater flexibility, access to global talent pools, and improved employee retention. Drawing on modern leadership theories and recent empirical studies, the article offers strategies for effective leadership in the hybrid era—ranging from transparent communication, outcome-based leadership, trust-building and team engagement, the use of collaborative technologies, to the critical role of empathy and adaptability. Case studies and empirical data, both from global contexts and Indonesia, are included to enrich the discussion. The article concludes that hybrid work is not a temporary trend but a permanent transformation in the world of work; hence, leaders are required to be adaptive and innovative for organizations to achieve optimal performance within this new paradigm.